A history of Islam in Indonesia : unity in diversity - Kersten, Carool (Edinburgh : Edinburgh University Press, 2017)
In this survey Carool Kersten presents the Islamisation of Indonesia from the first evidence of the acceptance of Islam by indigenous peoples in the late thirteenth century until the present day. He provides comprehensive insight into the different roles played by Islam in Indonesia throughout history, including the importance of Indian Ocean networks for connecting Indonesians with the wider Islamic world, the religion's role as a means of resistance and tool for nation-building, and postcolonial attempts to forge an 'Indonesian Islam'. -- From back cover.
Includes bibliographical references (pages 180-191) and index.
Print version record.
Added to collection customer.56279.3
Keywords: Islam -- Indonesia -- History; Islam -- Indonesia -- Historiography; Islam and state -- Indonesia; Islam; Islam and state; Islam -- Historiography; Indonesia; RELIGION / Islam / General; History; Electronic books